Implementasi Konsep Pendidikan Humanistik Dalam Perspektif Al-Qur’an Surat Al-Isra’ AYAT 70 - Dewi Ratnawati; Ahmad Zainal Abidin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
Reality that occurs related to the role of the environment in shaping the learner's personality is largely incompatible with the concept of humanistic education. The implications of the negative environmental role have an impact on moral degradation. Moral degradation of students includes free sex, crime, loss of respect to educators, and the loss of moral values ​​in students. There are external and internal factors in the emergence of moral degradation students. The existence of humanistic education is as a fortress to prevent moral degradation. The focus of this study is on the concept of humanism education, the influence of humanism education on students' social interaction, the humanism education in the perspective of Al-Isra: 70, and the implementation of humanism education according to Al-Isra: 70 in the education of learners. This research is formed through library research with content analysis approach. The researcher finds that activities carried out by students in the learning process based on norm in the rules on educational institution. The activity can be formed as social interactions to develop character, abilities and talents. That are possessed by students formed on Pancasila and religious values.